Interpretation of Interfaith and/or Belief Marriage by Judges: Disparity and Legal Vacuum: Penafsiran Perkawinan Beda Agama dan/atau Kepercayaan Oleh Hakim: Disparitas dan Kekosongan Hukum - Sanjaya, Umar Haris (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
Judges experience disparities in interpreting marriages of different beliefs and/or religions, resulting in different legal products, both determinations made. There is a difference between granting and rejecting. Interestingly, the understanding of the Constitutional Court judges and judges at District Courts has a significant disparity where one says there is a legal vacuum and the other is clear in accordance with the law. This study concerning a disparity in interfaith marriages in its determination and the legal vacuum of different-faith marriages created by judges in court. This study concludes that in practice judges in court in giving considerations believe there is a legal vacuum against marriages of different beliefs, as a result judges determine whether there is a disparity determination that is granted or not. The Constitutional Court itself interprets its decisions (2014 and 2022) that interfaith marriages are clear and do not constitute a legal vacuum in its enforcement.